Phase segregation mechanisms of small molecule‐polymer blends unraveled by varying polymer chain architecture. (8th June 2021) - Chen, Jihua; Das, Sanjib; Shao, Ming; Li, Guoliang; Lian, Huada; Qin, Jian; Browning, James F.; Keum, Jong K.; Uhrig, David; Gu, Gong; Xiao, Kai
Abstract: As phase separation between the small‐molecule semiconductor and the polymer binder is the key enabler of blend‐based organic field‐effect transistors (OFETs) fabricated by low‐cost solution processing, it is crucial to understand the underlying phase separation mechanisms that determine the phase morphology, which significantly impacts device performance. Beyond the parameter space investigated in previous work, here we investigate the formation of blends by varying the branch architecture of the polymer binder and by shortening the solvent dry time using ultrasonic spray casting. The phase morphologies of the resulting blend films have been thoroughly characterized with a variety of techniques in three dimensions over multiple length scales, including AFM, energy‐filtered transmission electron microscope, and neutron reflectivity, and have been correlated with electrical transport performance. From the results, we have inferred that the phase morphology is kinetically determined, limited by the inherent slow movement of polymer macromolecules. The kinetic picture, supported by molecular dynamics modeling, not only consistently explains our observations but also resolves inconsistencies in previous works. The achieved mechanistic understanding will guide further optimization of blend‐based organic electronics, such as OFETs and organic photovoltaics. Abstract : We investigate the phase separation mechanism of the small‐molecule semiconductor and the polymer composites for high‐performance organic field‐effect transistors using a variety of techniques across multiple length scales, including atomic force microscope, energy‐filtered transmission electron microscope, and neutron reflectivity, and reveal that the phase morphology is kinetically determined, limited by the inherent slow movement of polymers, which is supported by molecular dynamics modeling.